The impact of competitively complex exercises in the development of some offensive and defensive skills for young handball players - Mohammed Headan, Hussam; Hkem Mohamed, Sardar (International Journal of Psychosocial Rehabilitation, 2020)
The great development witnessed by handball game around the globe was the result of researching modern training methods that seek to achieve the training goals of the game and the economy with the efforts made and the time spent in training to serve to improve the level of technical and physical performance of theplayers. Complex exercises are widespread exercises which are of great importance in achieving training goals better than individual exercises, because the content of the exercise contains two or more types of exercise whether it is skill skills or physical skills or physical,and this will work to economy the time spent in training and help to develop skills and physical qualities better, that skill complex exercises that combine skills or more in one exercise characterized by interconnected Skills and the sequence of these skills according to the nature of the actual performance in the sports activity practice so that the player can master the motor sentences and the interconnection of skilled technical performance better through the sequence or motor course of these skills